Exploring the meaning of work in the context of organizational culture - Stapley, Lionel F. (Znaczenie pracy w kontekście kultury organizacyjnej, 2016)
The aim of this paper is to shed some light on the way that taking a group-as-a-whole approach; encompassing organizational culture; enables us to gain a different understanding of the meaning of work: one which is significantly different from an approach which takes the individual as the object of study. Most importantly; the paper will seek to answer the fundamental questions of how does culture develop; why do we develop a culture; and what is the purpose of a culture? An understanding of culture will serve as the point of departure to apply the hypothesis by showing how the processes of childhood can be linked to adult societal behaviour; and in doing so demonstrate the vital role that culture plays in our everyday lives. The theory will then be applied to two other highly valuable theories that take a group approach to the meaning of work. Namely; ‘social systems as a defence against anxiety’ [Menzies Lyth 1988; Jaques 1955]; and ‘sentient groups’ [Miller; Rice 1967]; where I shall suggest that they are more helpfully regarded as variations of organizational culture; and that when seen in this light they become more meaningful which opens up the possibility of working with these dynamics. The paper will conclude by applying the theory to a series of vignettes which will show that when the meaning of work is considered in the context of organizational culture; we are able to develop a different and deeper appreciation of the dynamics at play
Management Forum, 2016, vol. 4, no. 3, s. 23-28
Keywords: organizational culture; meaning of work; sentient groups; social systems as a defence against anxiety; kultura organizacyjna; znaczenie pracy; czująca grupa; systemy społeczne jako obrona przed lękiem